Effects of pre and post freezing treatments on barramundi (Lates calcarifer, Bloch) fillet quality - Younus Zakhariya, Sona (Curtin University, 2014)
The effects of pre-freezing treatments such as time-temperature abuse, use of ice, freeze–thaw cycles, use of polyphosphate and post freezing treatments such as glazing and packaging were assessed on the microbiological and physiochemical properties of barramundi (Lates calcarifer) fillets. The results indicated that the use of sodium tripolyphosphate, constant temperature and use of ice in the form of slurry can improve the shelf life of barramundi fillets.